2011
DOI: 10.1111/j.2042-7174.2010.00079.x
|View full text |Cite
|
Sign up to set email alerts
|

The General Practitioner–Pharmacist Collaboration (GPPC) study: a randomised controlled trial of clinical medication reviews in community pharmacy

Abstract: Clinical medication reviews in collaboration with general practitioners can have a positive effect on the Medication Appropriateness Index. However, pharmacist withdrawal from the study suggests that community pharmacy may not be an appropriate environment from which to expand clinical medication reviews in primary care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
167
0
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(171 citation statements)
references
References 47 publications
2
167
0
2
Order By: Relevance
“…Because prescribers worked external to the health authority, did not have direct interaction with the pharmacist, and did not build collaborative relationships with the pharmacist, the acceptance rate of pharmacist recommendations among prescribers was low. This rate was similar to rates seen in programs where pharmacists were not integrated into the prescriber teams 16,27,28 and was much lower than rates documented in other settings, where the pharmacist was part of the prescriberbased team. 6,29,30 If this service were to become permanent, a concentrated effort to engage prescribers from the beginning would be crucial.…”
Section: Discussionmentioning
confidence: 51%
“…Because prescribers worked external to the health authority, did not have direct interaction with the pharmacist, and did not build collaborative relationships with the pharmacist, the acceptance rate of pharmacist recommendations among prescribers was low. This rate was similar to rates seen in programs where pharmacists were not integrated into the prescriber teams 16,27,28 and was much lower than rates documented in other settings, where the pharmacist was part of the prescriberbased team. 6,29,30 If this service were to become permanent, a concentrated effort to engage prescribers from the beginning would be crucial.…”
Section: Discussionmentioning
confidence: 51%
“…Although the teams were significantly effective in reducing agitated behaviour and pain of the residents, no effect was found on the level of collaboration and coordination itself [28]. In two out of three studies [293031] interventions targeting pharmaceutical care including general practitioners and pharmacists showed significant effects. In the study of Denneboom et al (2007) pharmacists suggested the changes in medication to the general practitioners after medication review.…”
Section: Resultsmentioning
confidence: 99%
“…Clinical medication reviews in collaboration with general practitioners can have a significant positive effect on the ‘Medication Appropriateness Index’. However pharmacist withdrawal from the study suggest that community pharmacy may not be an appropriate environment from which to expand clinical medication reviews in primary care [29]. Interviewing patients, development and implementation of pharmaceutical care plans together with patients’ general practitioners and monthly medication reviews with patients performed by pharmacists did not reach any significant changes in appropriateness of prescribing medication [31].…”
Section: Resultsmentioning
confidence: 99%
“…A randomized controlled trial in New Zealand showed community pharmacists who collaborated with general practitioners improved medication-related outcomes, but there was high pharmacist withdrawal from the trial due to business operations and perceived relationship difficulties with general practitioners. 15 In the U.S., one study described a medication therapy management service implemented in 13 community pharmacies. While provider outreach was a strong focus for year 2 of the project, there was limited discussion and detail regarding interaction with providers and how providers were part of the program's design.…”
Section: Collaboration Opportunities For Community Pharmacistsmentioning
confidence: 99%